2018
DOI: 10.3892/mmr.2018.9081
|View full text |Cite
|
Sign up to set email alerts
|

miR‑23a downregulation modulates the inflammatory response by targeting ATG12‑mediated autophagy

Abstract: Autophagy, part of the innate immune defense mechanisms, is activated during the initial phase of septic insult. Previous studies indicated that micro (mi)RNAs are additionally involved in the host response to sepsis; however, the association between miRNAs and autophagy during this process is not fully understood. To study the role of miRNA (miR)-23a in autophagy initiated by sepsis, macrophages treated with lipopolysaccharides, in addition to blood samples from patients, were evaluated for miR-23a expression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 37 publications
2
15
0
Order By: Relevance
“…There are not many reports on the role of miRNA-23a on the regulation of inflammation. Interestingly, during septic insult, miRNA-23a expression was found to be decreased which was associated with increased autophagy and suppression of inflammatory mediators ( Si et al, 2018 ). In this study, miRNA-23a was shown to target Autophagy related 12 (ATG12), which regulates autophagy ( Si et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…There are not many reports on the role of miRNA-23a on the regulation of inflammation. Interestingly, during septic insult, miRNA-23a expression was found to be decreased which was associated with increased autophagy and suppression of inflammatory mediators ( Si et al, 2018 ). In this study, miRNA-23a was shown to target Autophagy related 12 (ATG12), which regulates autophagy ( Si et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…For example, miR-145 is highly expressed in vascular smooth muscle cells and has been reported to promote their switching to neointimal proliferating cells 105,106 and to regulate the transforming growth factor-β signalling pathway 103 . Increased levels of miR-23a contribute to cardiomyocyte apoptosis and may promote inflammatory responses by blocking macrophage autophagy activity 107,108 . However, improved understanding and characterization of the molecular and cellular mechanisms underlying the different roles of miRs during Kawasaki disease require further studies with animal models.…”
Section: Pathophysiology Of Kawasaki Diseasementioning
confidence: 99%
“…ATG12 directly promotes phagocytic elongation and autophagosome maturation, and can be targeted by miR-23a. In sepsis, down-regulation of miR-23a mitigates the inhibition of autophagy, leading to the suppression of inflammatory mediator (Si et al, 2018). The study found that over-expression of miR-335-5p induced autophagy by activating the AMPK/ULK1 (AMP-activated protein kinase/unc-51 like autophagy activating kinase 1) signaling pathway and attenuating the inflammatory response in a mouse model of sepsis (Gao et al, 2018).…”
Section: Regulation Of Autophagy In Sepsis and Its Mechanism Of Actionmentioning
confidence: 99%